The extent of intestinal involvement is closely related to the severity of IgAV: a risk stratification study based on CT - Yuanqiu Li; Ziman Xiong; Yufan Wang; Yuchen Jiang; Yaqi Shen; Xuemei Hu; Daoyu Hu; Zhen Li (Annals of Medicine)
Objectives To analyze the differences in clinical manifestations between children and adults with intestinal involvement in IgAV and to identify the specific subtypes requiring particular attention.Methods A systematic review of the HIS system was conducted on patient data from four centers at Tongji Hospital between January 2015 and October 2022. Patients with a diagnosis of IgAV with intestinal involvement were further analyzed. Clinical manifestations, laboratory data, and CT findings at the time of initial hospitalization were recorded. The differences in clinical manifestations between children and adults were analyzed. The extent of intestinal involvement, linked to disease severity, was quantitatively assessed by evaluating the number of affected intestinal segments on CT imaging. Laboratory markers that could reflect severe intestinal involvement were explored. Furthermore, patients were classified based on the sites of involved intestinal segments: L1 type (duodenum and/or jejunum), L2 type (ileum), L3 type (duodenum and/or jejunum and ileum), and L4 type (limited to the colorectum). A comparison of the first three types was performed.Results A total of 148 patients were enrolled (67 children and 81 adults). The proportion of joint pain and renal involvement was higher in adults. D-dimer level was an independent risk factor for severe intestinal involvement (OR = 1.104, p = .016). In the first three types patients based on the sites of involved intestinal segments, it found that L3 type patients had a longer hospital stay.Conclusion With the exception of joint pain and renal involvement, there were no significant differences in clinical symptoms between children and adults. CT imaging provided objective insights into the extent of intestinal involvement, which correlated with disease severity. Patients with widespread small bowel involvement displayed a more severe disease state.